Instrumental activities of daily living and self-rated health in community-dwelling older adults: cross-sectional findings from the HUNT Study (HUNT4 Trondheim 70+) - Anne Kusk Pedersen; Linda Ernstsen (BMC Geriatrics)
Abstract Background The population of older adults is growing, posing new challenges for society and healthcare services. Instrumental Activities of Daily Living (IADL) describe individuals’ ability to handle more complex activities in their daily life and to the extent to which they can live independently. Self-rated health (SRH) is a frequently used metric in health research and is a robust predictor for institutionalization and mortality. Therefore, the purpose of this study is to investigate the association between IADL function and SRH among community-dwelling older adults in Norway, and to determine the influence of cognitive function. Methods A total of 1104 community-dwelling adults aged 70 or older participating in the population-based Trøndelag Health Study (HUNT) 4 Trondheim 70 + were included. Logistic regression was used to examine the association between IADL function and SRH. IADL function was divided into two groups, IADL limitation (requiring help to complete one or more daily activities) and no IADL limitation. SRH were dichotomized into good and poor SRH. Results Of the 1104 included participants 127 (11.5%) experienced IADL limitation. After adjustment for gender, age, cohabiting status, educational level, physical activity, gait speed, grip strength, depressive symptoms, limiting long-term illness and cognitive function, participants with IADL limitation had significantly higher odds of poor SRH compared to those without IADL limitation (odds ratio 3.26, 95% confidence interval 1.89–5.61, p < 0.001). Conclusions These cross-sectional results from an urban population of community-dwelling older adults showed a strong association between IADL limitation and poor SRH independent of cognitive function, emphasizing the importance of investigating the prospective relationship between IADL and SRH. Intervention studies are needed to confirm whether improving IADL function can impact SRH in older adults. Clinical trial number Not applicable.